A stimuli-responsive and chemically tunable organic microcrystal laser switch. Issue 6 (21st December 2018) - Cai, Xin; Xu, Zhenzhen; Zheng, Xiaolin; Ran, Chenhui; Liu, Peng; He, Xianxiong; Jin, Xue; Liao, Qing; Fu, Hongbing
Abstract : We demonstrated a stimuli-responsive and chemically switchable organic microbelt laser through reversible protonation–deprotonation reactions. Abstract : We demonstrated a stimuli-responsive and chemically switchable organic microbelt laser through reversible protonation–deprotonation reactions. The parent microbelt cavity together with the optically allowed 0–1 transition of H-aggregates enables a microlaser to operate at 585 nm. Upon HCl vapor treatment, the protonation of surface molecules shifts the lasing wavelength to 560 nm, generating an intensity contrast ratio >10 5, accompanied by a sharp color change from orange (deprotonated) to green (protonated). When treated with HCl–NH3 vapor, the protonation–deprotonation reactions lead to a reversible microlaser switch between 585 nm and 560 nm with good reproducibility and photostablity, making them attractive in high-throughput chemical and biological sensing applications.